Evaluation of the supply of antifungal medication for the treatment of vaginal thrush in the community pharmacy setting: a randomized controlled trial - Schneider CR; Emery L; Brostek R; Clifford RM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Background: The Pharmaceutical Society of Australia have developed "guidance" for the supply of several medicines available without prescription to the general public. Limited research has been published assessing the effect of these guidelines on the provision of medication within the practice of pharmacy. Objectives: To assess appropriate supply of non-prescription antifungal medications for the treatment of vaginal thrush in community pharmacies, with and without a guideline. A secondary aim was to describe the assessment and counseling provided to patients when requesting this medication.Methods: A randomized controlled trial was undertaken whereby two simulated patients conducted visits to 100 randomly selected community pharmacies in a metropolitan region. A product-based request for fluconazole (an oral antifungal that has a guideline was compared to a product-based request for clotrimazole (a topical antifungal without a guideline). The same patient details were used for both requests. Outcome measures of the visits were the appropriateness of supply and referral to a medical practitioner. Results: Overall 16% (n=16) of visits resulted in an appropriate outcome; 10% (n=5) of fluconozaole requests compared with 22% (n=11) of clotrimazole requests (chi-square=2.68, p=0.10). There was a difference in the type of assessment performed by pharmacy staff between visits for fluconazole and clotrimazole. A request for clotrimazole resulted in a significant increase in frequency in regards to assessment of the reason for the request (chi-square=8.57, p=0.003), symptom location (chi-square=8.27, p=0.004), and prior history (chi-square=5.09, p=0.02).Conclusions: Overall practice was poor, with the majority of pharmacies inappropriately supplying antifungal medication. New strategies are required to improve current practice of community pharmacies for provision of non-prescription antifungals in the treatment of vaginal thrush.